Value creation or destruction? Hedge funds as shareholder activists - Clifford, Christopher P. (Journal of Corporate Finance, 2008)
I examine the effects of shareholder activism by hedge funds from 1998–2005. When hedge funds accumulate more than 5% of a firm, they must file a regulatory disclosure with the SEC that indicates whether their investment intentions are active or passive. Firms which are targeted by hedge funds for active purposes earn larger excess stock returns and improvements in operating performance (ROA) than a control group of firms that are targeted by the same hedge funds for passive purposes. These operational improvements appear to be driven by the divestiture of under-performing assets. I examine the organizational structure of the hedge funds and find that funds engaging in activism are more likely to have longer lock-ups and withdrawal notification periods than their non-activist peers; indicating that liquidity concerns may be an important determinant in the efficacy of activism. Finally, I document that the returns to the hedge fund are larger for their active blocks than their passive blocks, indicating that activist shareholders may use higher returns to mitigate the cost of their monitoring effort.